Cathar "Time-Focused Dualism"—An Argument for the Eastern Origins of Catharism - Czarnecki, Piotr (The catholic historical review, 2021)
The starting point of this article is the conception of Bernard Hamilton from 1974 assuming that the Bogomil Church of Drugunthia was formed under Paulician influence. Its radically dualistic doctrine was later accepted by some Cathars described in the sources as belonging to the Drugunthian order (ordo Drugonthiae). The article attempts to verify this concept through doctrinal analysis, and to answer the question whether distinctive features of the Paulician doctrine can be found in the teachings of the Cathars of the Drugunthian order. Analysis of sources of various provenance—polemical, inquisitorial and Cathar (the so called "Manichaean Treatise")—show clearly that traces of specific Paulician "time-focused dualism" can be found in Cathar teachings, which confirms Hamilton's conception and is an important argument for the Eastern origins of Catharism.